The Effect of The Collaboration of Jigsaw Learning Model with Problem-Based Learning Model on Students' Critical Thinking Skills Post COVID-19 Pandemic - Istikhomah Nindy Kusuma; Harini Harini; Salman Alfarisy Totalia (Universitas Negeri Surabaya, 2023)
Post COVID-19 Pandemic conditions pose a challenge to the world of education, especially for teachers so that they can encourage students to think critically after studied from home for so long. The purpose of this research is to determine the effect of the collaboration of jigsaw learning model with problem-based learning (PBL) model on students’ critical thinking skills in economics subject at SMA Negeri 2 Surakarta post COVID-19 Pandemic. The reasearch method used a quasi experimental design type non-equivalent control group design. The research subject was 11th grade students of SMA Negeri 2 Surakarta who were divided into two sample class, namely experimental class and control class. The sampling technique used purposive sampling technique. Data collection techniques used tests, observation and documentation. The research data analysis techniques used hypothesis tests with paired sample t-test, independent sample t-test, and ANOVA. The result of this research showed that the application of the collaboration of jigsaw learning model with PBL model had positive and significant effect on students’ critical thinking skills in economics subject at SMA Negeri 2 Surakarta post COVID-19 Pandemic.